A (in)visibilidade dos trabalhadores com deficiência intelectual - Santos, Thamille Pereira dos (Universidade do Vale do Rio dos Sinos, 2025)
Considering the inclusion of people with disabilities in the labor market, this thesis questions how regulations on labor inclusion and statistics on living conditions, education, and employment allow us to visualize the conditions of young people and adults with disabilities and position them within this context. The objective is to understand, analyze, and problematize the inclusion of young people and adults with disabilities in the labor market. To this end, the study relies on the analysis of government statistical data from population, educational, labor, and institutional surveys conducted between 2010 and 2023, as well as federal regulations governing labor inclusion between 1989 and 2015. The reading of these materials and the problematization developed are based on a perspective of Foucauldian studies. Among the research findings, it is noteworthy that people with disabilities have low levels of education, which represents one of the main barriers to entering the labor market. Furthermore, when they do enter, they predominantly occupy low-skilled positions, receive the lowest salary ranges, and face a lack of labor rights, informality, prejudice, and stigma. This precarization is even more pronounced for individuals with intellectual disabilities, who experience greater inequalities within the group itself. The situation worsens when intersected with gender, income, race, age, and education level. The inclusive labor regulations and the latest data on work-related education reveal that education operates within an ableist logic, defining people with disabilities through the lens of incapacity, which contributes to low schooling levels. Moreover, these regulations reinforce inequalities and precarization by placing the sole responsibility for inclusion in the labor market on the person with disabilities. Vocational training is primarily aimed at placing individuals with disabilities in low-skilled jobs, without focusing on their professional development. The defended thesis argues that the processes of (in)visibility in public policies and statistics reinforce inequalities and precarization in the labor market for people with disabilities. When intersected with gender, race, age, and type of disability, these inequalities become even more pronounced, constructing a worker perceived as unproductive in contemporary society.

Tomando como contexto la inclusión de personas con discapacidad en el mundo del trabajo, la presente tesis cuestiona cómo las normativas sobre inclusión en el mundo del trabajo y las estadísticas sobre las condiciones de vida, escolaridad e inclusión en el mundo del trabajo permiten visualizar las condiciones de los jóvenes y adultos con discapacidad y posicionarlos en este mundo. Su objetivo es conocer, analizar y problematizar la inclusión de jóvenes y adultos con discapacidad en el mundo trabajo. Para ello, invertimos em el análisis de datos estadísticos gubernamentales sobre investigaciones poblacionales, educativas, laborales e institucionales en el período de 2010 a 2023 y de las normas federales que regulan la inclusión em el mundo del trabajo en el período de 1989 a 2015.La lectura de los materiales y la problematización desarollada se realizan desde una perspectiva de la estudios foucaultianos. Entre los encuntros de la investigación, se destaca que las personas con discapacidad tienem un bajo nivel de instrucción, lo que representa una de las principales limitaciones para el acesso al mundo del trabajo. Además, cuando ingresan a el mundo del trabajo, ocupan puestos que requieren bajas calificaciones, reciben osas menores remuneraciones y enfrentan la ausencia de derechos laborales, la informalidad, los prejuicio y el estigma. Esta precarización se agrava en el caso de las personas con discapacidad intelectual, quienes se ven aún más desiguales dentro del propio grupo. Esta precariedad se intensifica cuando existe uma interseccionalidad entre género, ingreso, raza, edad y nivel de educación. Las normativas inclusivas para el mundo del trabajo y los datos más recientes sobre capacitación para el trabajo muestran que la educación opera dentro de una lógica capacitista, definiendo a las personas con discapacidad em función de la incapacidad, lo que contribuye a la baja escolarización. Además, las normativas reverberan desigualdades y la precariedad, colocando a las personas con discapacidad como las únicas responsables de su inclusión en el mundo del trabajo. La formación para el trabajo tiene como objetivo inserción, sin apuntar a su profisionalizaci[on. La tesis defende que los procesos de (in)visibilidad en las políticas públicas y las estadísticas refuerzan las desigualdades y la precariedad en el mundo del trabajo de las personas con discapacidad. Cuando se suman las intersecciones de género, raza, edad y tipo de discapacidad, estas desigualdades se agravan aún más, constituyendo un trabajador considerado no productivo para la sociedad contemporánea.
Keywords: Deficiência intelectual; Precarização; Desigualdades; Mundo do trabalho; Intellectual disability; Precarization; Inequalities; Labor market; Discapaidad intelectual; Precariedade; Mundo del trabajo; ACCNPQ::Ciências Humanas::Educação